Development of Interactive E-Book Based on Project Based Learning-STEM to Improve Creative Thinking and Collaboration Skill in Vocational Schools - Sayyid Muhamad Alwi; Eges Triwahyuni; Hariyanto (Postgraduate, University of Mataram, 2025)
The participation of SMK students is driven by employment goals and in response to market constraints and personal challenges, hence the need for flexibility in vocational training. The purpose of preparing the research is the development of interactive e-books, product feasibility, and the effectiveness of using Interactive E-books in class X DPIB at SMKN 2 Jember. This research is a Research and Development (R&D), in the form of an ADDIE model approach, which consists of five levels, namely analysis, design, development, implementation, and evaluation. The results of the validation assessment show the percentage of the feasibility of the media component of 94.67% and the material component of 95.56%, can be categorized as “Very Valid”. The results of product feasibility tested on students, have a feasibility percentage of 99.01%, indicating that the Interactive E-book is “Very Feasible”. The results of the analysis test on the pretest and post-test scores showed an average increase of 36.16 with an N-Gain of 86.71 in the high category. These results show that X DPIB SMK students are better when applying media in the form of Project Based Learning-STEM interactive e-books and can improve creative thinking and collaboration skills.